Review of the most widely used post-training recovery techniques to reduce the incidence of chronic fatigue in football players - Gaviria Marulanda, Alexandrea (2020)
Introduction: The following article aims to highlight the use of the most used recovery techniques in soccer players after training and sports competition, which reduce the incidence of chronic fatigue and in turn, the occurrence of musculoskeletal injuries, improving sports performance and avoiding overtraining syndrome due to lack of recovery. Objective: To investigate the different recovery protocols or strategies most used in soccer post-training and the work of the sports physiotherapist in multidisciplinary teams. Methods: Databases such as Pubmed, Science direct, Scielo, Google Scholar, were reviewed through an exploratory review, generating an analysis against the effectiveness and impact at a physiological and psychological level. Results: The results allowed to group the recovery techniques into the group of active recovery methods and that of passive recovery methods that favor the recovery of the athlete after training sessions and in competition periods. Conclusion: Different authors have pointed out the relevance of recovery in sports performance and especially in this type of sport, since it constitutes one of the basic principles of training, in which injuries in soccer can be prevented from different aspects.